Sensory and microbiological evaluation of Drâa goat cheese and study of its stability during storage - Noutfia Y.; Alem C.; Filali Zegzouti Y. (Innovation for sustainability in sheep and goats, 2019)
Goat cheese in the oasis regions of Morocco remains a poorly characterized and studied product, in spite of the genetic potential of the oases and the efforts deployed by the Moroccan State to promote this dairy product. The present work aims to contribute to the characterization of Drâa goat cheese through (i) sensory and microbiological evaluation and (ii) studying stability of this cheese during storage. Thus, 8 cheese bars (from a milk mixture of at least 2 goats / cheese tablet) have been produced at the laboratory scale. The microbiological and sensorial characteristics of cheese were determinated. The stability study was focused on the monitoring of 3 parameters: fungal flora, drying rate and lactic acid content at intervals of 0, 8 and 16 days of storage. The results show that Drâa goat cheese contains (CFU/ml) respectively: 8,33.10+08, 9,35.10+06, 2,17.10+04 and 6,83.10+03 of lactic acid bacteria, psychrotrophic bacteria, yeast and Molds. Sensory analysis revealed a highly significant difference between the Drâa cheese and that produced with Alpine goat milk. The scores obtained by the hedonic test are 5.3/10 for the odor, 4.9/10 for the taste and 5.9/10 for the consistency. For the storage of Drâa cheese, it was concluded that the acidity (P = 0.03) and the fungal flora, yeast (P = 0.004) and molds (P = 0.003), increased with a significant manner during the 16 days of cold storage; however, no significant difference was recorded for water content.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)